REPRESENTAÇÕES: A POLÍCIA MILITAR FEMININA NO PARANÁ (1979-1984) (Revista de História Regional, 2007)
The text refers to the womens entrance in PMPR, at the end of the 1970s, an institution which belonged exclusively to men. The texts of the legislation that instituted womens presence in the Military Police was one of the elements of the construction of the feminine police in Paraná. Starting from a columnists of the city of Ponta Grossa chronicles, the article identifies how he looked at thepolicewomen group formed in the city between 1983 and 1984,when a platoon of the feminine police was implanted in thecity. Since he was both built by and builder of the society inwhich he lived, his glance was not unique, but shared byother men.